2020
DOI: 10.21203/rs.3.rs-35951/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Utilization of Maternity Waiting Homes to Increase Uptake of Immediate Postpartum Family Planning in Primary Health Care Facilities in Ethiopia

Abstract: Background: Maternity waiting home (MWH) within primary health care facilities is an ideal platform to reach women with family planning education and counseling. MWH users interact with health care providers on a regular basis throughout their waiting period and can prepare to initiate family planning method of their choice immediately after childbirth. However, to date, there has been no clear evidence about the use of MWHs to increase uptakes of immediate postpartum family planning (IPPFP). Therefore, the ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Nine of the studies showed a correlation between MWHs and improved access to maternal health services, particularly skilled childbirth care [14,28,30,32,33,37,43,45,46]. MWHs strategy has been a means for increasing the demand for maternity care, improving geographic access to childbirth, addressing the second delay, delay in reaching a health center and enabling more timely and comprehensive obstetric care [14,28,33,37,39,46].…”
Section: Better Access To Maternal Health Services and Health Informa...mentioning
confidence: 99%
“…Nine of the studies showed a correlation between MWHs and improved access to maternal health services, particularly skilled childbirth care [14,28,30,32,33,37,43,45,46]. MWHs strategy has been a means for increasing the demand for maternity care, improving geographic access to childbirth, addressing the second delay, delay in reaching a health center and enabling more timely and comprehensive obstetric care [14,28,33,37,39,46].…”
Section: Better Access To Maternal Health Services and Health Informa...mentioning
confidence: 99%
“…Institutional delivery and child immunization are the determinants most related with voluntary use of IPPIUCD [ 12 , 13 ]. Different articles have verified the necessity of effective counseling and community participation to improve IPPIUCD use [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Institutional delivery and child immunization are the determinants most related with voluntary use of IPPIUCD [ 12 , 13 ]. Different articles have verified the necessity of effective counseling and community participation to improve IPPIUCD use [ 12 , 13 , 14 , 15 ]. The difficulties identified for IPPIUCD use were perceiving low risk of conception during the postpartal period among health care professionals and most importantly women needed to use the method, small rate of institutional deliveries, and cultural restrictions [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 Different primary studies were conducted in Ethiopia and estimated the prevalence of maternity-waiting home utilisation. [13][14][15][16][17][18][19][20][21][22][23][24] According to these separate studies, the prevalence of maternity-waiting home use among Ethiopian women ranges from 7% 16 to 68.8%, 17 and there was a significant variation and inconsistency in the prevalence of maternity-waiting home use among women across the country. Similarly, the factors associated with the utilisation of MWHs were different from study to study.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the factors associated with the utilisation of MWHs were different from study to study. [13][14][15][16][17]19,[21][22][23]25,26 The variation mentioned above in the prevalence and determinants of MWH use among Ethiopian women needs to be pooled and utilised at the national level. As a result, it is critical to have summarised evidence on the prevalence rate and determinants of MWH use among women.…”
Section: Introductionmentioning
confidence: 99%